Optimization of Enzyme-Assisted Mechanical Extraction Process of Hodgsonia heteroclita Oilseeds and Physical, Chemical, and Nutritional Properties of the Oils - Piseskul J. (2023)
Hodgsonia heteroclita subsp. Indochinensis W.J.de Wlide & Duyfjes (or Making in Thai) is a neglected and underutilized crop (NUC) with high fat containing nuts. In this study, the enzyme-assisted mechanical extraction of H. heteroclita seed oil was investigated using response surface methodology (RSM) to predict the optimal fat extraction conditions. The most efficient enzyme used in the experiment was a mixture of Flavourzyme® and Viscozyme® (1:1, w/w). The predicted maximum oil yield was 46.44%, using the following extraction conditions: 2.98% (w/w) enzyme loading, 48 °C incubation temperature and 76 min of incubation time. H. heteroclita seed oil obtained from heat and enzymatic pretreatments exhibited the highest lightness and viscosity. The chemical properties of this seed oil, including water and volatile compounds (≤0.2% w/w), acid value (≤4.0 mg KOH/g), peroxide value (≤15 mEq of active oxygen/kg) and soap content (≤0.005% w/w), were within the acceptable levels specified by the Codex Alimentarius (2019). H. heteroclita seed oil obtained from heat and enzymatic pretreatments contained the highest content of δ-tocopherol (88.29 mg/100 g) and omega-6 fatty acids (48.19 g/100 g). This study is the first to report on the enzyme-assisted mechanical extraction of H. heteroclita oilseeds as a promising plant material for vegetable oil production.